2019
DOI: 10.1096/fba.2019-00021
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles selectively treat triple‐negative breast cancer cells without affecting non‐malignant breast epithelial cells in vitro and in vivo

Abstract: Silver nanoparticles (AgNPs) show promise for treatment of aggressive cancers including triple‐negative breast cancer (TNBC) in preclinical cancer models. For clinical development of AgNP‐based therapeutics, it will be necessary to clearly define the specific physicochemical features of the nanoparticles that will be used, and to tie these properties to biological outcomes. To fill this knowledge gap, we performed thorough structure/function, mechanistic, safety, and efficacy studies to assess the potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 76 publications
(152 reference statements)
3
70
1
Order By: Relevance
“…Previous studies indicated that the size and coating of AgNPs could affect the toxicity profile of AgNPs in colorectal cancer and murine monocyte/macrophage cell lines [40]. In contrast, we previously observed that size, shape, and coating of AgNPs did not affect the toxicity profile of AgNPs in triple negative breast cancer cell lines [41]. Thus, the toxicity of AgNPs is determined by both the physical and chemical properties of AgNPs and by the metabolic phenotype of cells.…”
Section: Methodsmentioning
confidence: 91%
“…Previous studies indicated that the size and coating of AgNPs could affect the toxicity profile of AgNPs in colorectal cancer and murine monocyte/macrophage cell lines [40]. In contrast, we previously observed that size, shape, and coating of AgNPs did not affect the toxicity profile of AgNPs in triple negative breast cancer cell lines [41]. Thus, the toxicity of AgNPs is determined by both the physical and chemical properties of AgNPs and by the metabolic phenotype of cells.…”
Section: Methodsmentioning
confidence: 91%
“…Tumor cells exhibit intact cell structure under light microscope, such as round nuclei, intact nuclear membrane, homogeneous chromatin, normal mitochondria and rough endoplasmic reticulum 40 . The ultrastructural changes of AgNPs-exposed tumor cells are in a dose- and time-dependent manner 246 . Generally, the higher the concentration of AgNPs and the longer the exposure time, the more serious the damage of cell ultrastructure.…”
Section: Medical Applications Of Agnpsmentioning
confidence: 99%
“…AgNPs have been investigated intensively regarding their promising anticancer effects exhibited in different human cancer cell lines, such as endothelial cells, IMR-90 lung fibroblasts, U251 glioblastoma cells and MDA-MB-231 breast cancer cells [40,106,155,156]. AgNPs showed great promises as effective anti-tumor drug-delivery systems [157].…”
Section: Clinical Applicationmentioning
confidence: 99%